System-thinking progress in engineering programs: A case for broadening the roles of students - Tamir, Ram; Ben-Zvi Assaraf, Orit; Maman, Shimrit (Frontiers in Education, 2023)
Complex systems are prevalent in many scientific and engineering disciplines, which makes system thinking important for students of these fields. Duchifat 3 is a unique engineering educational program, where high school students designed, assembled, and tested a nano-satellite. This study applied qualitative methods to explore how the participants’ systems-thinking developed during the program. Participants were interviewed using the repertory grid interview, and a semi structured interview at the beginning and at the end of the project, while various observations were conducted throughout. While the participants were initially assigned narrow roles, each dealing with a single sub-system of the satellite, some chose to be involved with other sub-systems and aspects of the project. Our findings show that the broader the participants’ involvement was, the greater the progress they experienced in their systems-thinking. Participants who stayed focused on a single subsystem did not show progress, while participants who involved themselves with several sub-systems exhibited a more meaningful progress. Although the program design aimed to assign students to a narrow role to enable them to achieve the educational goals, from the perspective of systems-thinking this was counterproductive. These findings shed light on the design of engineering programs such as the one examined here in terms of systems-thinking development. We discuss the implications of the findings for similar programs and make suggestions for improvement.